Altered Cortical-Striatal Network in Patients With Hemifacial Spasm - Gao, Wenwen; Yang, Dong; Zhang, Zhe; Du, Lei; Liu, Bing; Liu, Jian; Chen, Yue; Wang, Yige; Liu, Xiuxiu; Yang, Aocai; Lv, Kuan; Xue, Jiajia; et al. (Frontiers in Human Neuroscience, 2021)
Objective: Hemifacial spasm (HFS) is a kind of motor disorder, and the striatum plays a significant role in motor function. The purpose of this study is to explore the alterations of the cortical-striatal network in HFS using resting-state functional magnetic resonance imaging (fMRI). Methods: The fMRI data of 30 adult patients with primary unilateral HFS (15 left-side, 15 right-side) and 30 healthy controls were collected. Six subregions of the striatum in each hemisphere were selected for functional connectivity (FC) analysis. One-sample t test was used to analyze the intra-group FC of the HFS group and the control group. Two-sample t test was used to compare the difference of FC between the two groups. The correlation between the abnormal FC and severity of hemifacial spasm was evaluated by Spearman correlation analysis. Results: Compared to the controls, the striatal subregions had altered FC with motor and orbitofrontal cortex in HFS patients, respectively. The altered FC between striatal subregions and motor cortex was correlated with the spasm severity in HFS patients. Conclusions: The FC of the cortical-striatal network was altered in primary HFS, and these alterations were correlated with the severity of hemifacial spasm. This study indicated that the cortical-striatal network may play different roles in the underlying pathological mechanism of HFS.